Hryhorii Skovoroda in English-Language Studies and Translations - Zosimova, O.; Kniaz, H. (New Collegium, 2023)
In the context of Ukraine’s further European integration, the issue of popularizing our culture and understanding its achievements in terms of the world’s civilization progress is gaining particular relevance. The purpose of this research is to find out whether Hryhorii Skovoroda’s name is well-known to the readers and scholars in the USA, Canada, and the UK, and how his ideas and works were popularized in the English-speaking world. The present study shows that the research into Skovoroda’s philosophy and literary works in English-speaking countries began in the second half of the 20th century, primarily in the United States and Canada, as evidenced by the studies of Karen L. Black, Richard Hantula, Taras Zakydalskyi, George Kline, Natalia Pylypiuk, Stephen Scherer and others. In 1994 “An Anthology of Critical Articles” dealing with various aspects of H. Skovoroda’s work was published by Canadian Institute of Ukrainian Studies. This volume is a collection of symposium papers that focus on the unique figure of the Ukrainian writer from different perspectives: historical, social, literary, theological, philosophical, pedagogical, and linguistic. The book of papers also includes a vast bibliography of Skovoroda studies compiled by R. Hantula. In 1997 a special issue of the “Journal of Ukrainian Studies” was devoted to Hryhorii Skovoroda’s creative work, its sources, basic ideas, and the influence on further development of Slavic philosophy and literature. Translations of the philosopher’s texts into English, which also began to appear in the 1960–1970s, are an important factor contributing to the growing interest in H. Skovoroda’s work and the significant expansion of the circle of its researchers. To date, the writer's fables, some of his philosophical treatises, letters, as well as poetic works were translated. A breakthrough in the popularization of Skovoroda’s name in the English-speaking world is the translation of his collection of verses “The Garden of Divine Songs” and collected poetry (translated by Michael M. Naydan) as well as his complete correspondence (translated by Eleonora Adams and Michael M. Naydan), which were published in London in 2016. The overview of English-language studies and translations of Hryhorii Skovoroda’s works proves that Western scholars made a valuable contribution to the research on the philosopher’s legacy as well as popularization of his works by translating them into English.